2011
DOI: 10.1111/j.1540-5982.2011.01673.x
|View full text |Cite
|
Sign up to set email alerts
|

Domestic violence and women's autonomy in developing countries: theory and evidence

Abstract: This paper sets out a simple non-cooperative model of resource allocation within the household in developing countries that incorporates domestic violence as a vehicle for enhancing bargaining power. We demonstrate that the extent of domestic violence faced by women is not necessarily declining in their reservation utilities, or necessarily increasing in their spouses'. Using the National Family Health Survey data of India for 1998-99, we isolate the effect of domestic violence on female autonomy, taking into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
158
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(175 citation statements)
references
References 32 publications
14
158
2
1
Order By: Relevance
“…This result is consistent with the views of focus groups from villages in the north, which argued that living in the birthplace allows a woman to benefit from her family's and relatives' social support. The result found is in contrast to the findings of Mukesh Eswaran and Nisha Malhotra (2011), who used data from India. They found that a woman's freedom to decide about various aspects of her life declines in the presence of her own and her husband's natal family.…”
Section: Resultscontrasting
confidence: 85%
“…This result is consistent with the views of focus groups from villages in the north, which argued that living in the birthplace allows a woman to benefit from her family's and relatives' social support. The result found is in contrast to the findings of Mukesh Eswaran and Nisha Malhotra (2011), who used data from India. They found that a woman's freedom to decide about various aspects of her life declines in the presence of her own and her husband's natal family.…”
Section: Resultscontrasting
confidence: 85%
“…The bargaining power of a woman is determined both by individual factors such as the relative economic position or cultural expectations regarding male and female gender roles. (ESWARAN AND MALHOTRA 2011, GOODE 1971, HEISE 2012, JEWKES 2002, LEVINSON 1989.…”
Section: Theoretical Background and Literaturementioning
confidence: 99%
“…As a result, an increase in women's labour market income may increase the weight of her preferences in household resource allocation decisions. The increased bargaining power of women may improve her well-being or instead may increase household conflict as it decreases the husband's decisionmaking power (Eswaran & Malhotra, 2011). Anderson and Eswaran (2009) show that the effect of wage income on female autonomy is greater than that of non-labour income.…”
Section: Introductionmentioning
confidence: 98%
“…This supports the male backlash hypothesis argued in the sociology literature. Eswaran and Malhotra (2011) showed that domestic violence impinges on female autonomy for husbands with low outside options. Chin (2012) finds that female employment decreases domestic violence among Indian women with this result being explained by the fact that the empowerment effect is larger than the male dominance effect.…”
Section: Introductionmentioning
confidence: 99%